Effects of Hypertriglyceridemia With or Without NEFA Elevation on β-cell Function and Insulin Clearance and Sensitivity - Tricò, Domenico; Rebelos, Eleni; Astiarraga, Brenno; Baldi, Simona; Scozzaro, Tiziana; Sacchetta, Luca; Chiriacò, Martina; Mari, Andrea; Ferrannini, Ele; Muscelli, Elza; Natali, Andrea (The journal of clinical endocrinology and metabolism, 2025)
Hypertriglyceridemia is a risk factor for developing type 2 diabetes (T2D) and might contribute to its pathogenesis either directly or through elevation of nonesterified fatty acids (NEFAs). This study aimed at comparing the glucometabolic effects of acute hypertriglyceridemia alone or combined with NEFA elevation in subjects without diabetes. Twenty-two healthy lean volunteers underwent 5-hour intravenous infusions of either saline or Intralipid, without (n = 12) or with heparin (I + H; n = 10) to activate the release of NEFAs. Oral glucose tolerance tests (OGTTs) were performed during the last 3 hours of infusion. Insulin sensitivity, insulin secretion rate (ISR), model-derived β-cell function, and insulin clearance were measured after 2 hours of lipid infusion and during the OGTTs. In fasting conditions, both lipid infusions increased plasma insulin and ISR and reduced insulin clearance without affecting plasma glucose and insulin sensitivity. These effects on insulin and ISR were more pronounced for I + H than Intralipid alone. During the OGTT, the lipid infusions markedly impaired glucose tolerance, increased plasma insulin and ISR, and decreased insulin sensitivity and clearance, without significant group differences. Intralipid alone inhibited glucose-stimulated insulin secretion (ie, β-cell glucose sensitivity) and increased β-cell potentiation, whereas I + H had neutral effects on these β-cell functions. In healthy nonobese subjects, mild acute hypertriglyceridemia directly reduces glucose tolerance and insulin sensitivity and clearance, and has selective and opposite effects on β-cell function that are neutralized by NEFAs. These findings provide new insight into plausible biological signals that generate and sustain insulin resistance and chronic hyperinsulinemia in the development of T2D.